2019
DOI: 10.5194/gmd-12-613-2019
|View full text |Cite
|
Sign up to set email alerts
|

Topological data analysis and machine learning for recognizing atmospheric river patterns in large climate datasets

Abstract: Abstract. Identifying weather patterns that frequently lead to extreme weather events is a crucial first step in understanding how they may vary under different climate change scenarios. Here, we propose an automated method for recognizing atmospheric rivers (ARs) in climate data using topological data analysis and machine learning. The method provides useful information about topological features (shape characteristics) and statistics of ARs. We illustrate this method by applying it to outputs of version 5.1 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 32 publications
0
39
0
Order By: Relevance
“…Latitude-independent relative methods use one threshold based on the climatology of a given region and can be expected to produce larger gradients in AR statistics, which will likely be more similar to results produced by absolute methods. Furthermore, this paper includes one method based on machine learning (TDA_ML; Muszynski et al, 2019), which defies many of the threshold-based groupings outlined above. It is currently employed over the western Unites States but could be readily applied to other regions.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Latitude-independent relative methods use one threshold based on the climatology of a given region and can be expected to produce larger gradients in AR statistics, which will likely be more similar to results produced by absolute methods. Furthermore, this paper includes one method based on machine learning (TDA_ML; Muszynski et al, 2019), which defies many of the threshold-based groupings outlined above. It is currently employed over the western Unites States but could be readily applied to other regions.…”
Section: Methodsmentioning
confidence: 99%
“…For example, both "Lavers" and "Ramos" use time-dependent percentiles based on climatological IVT, and "Viale" imposes the restriction that an AR must be associated with a frontal system. The machine learning technique, "TDA_ML," produces AR frequencies below the median, possibly because the algorithm employed by Muszynski et al (2019) exhibits a fairly strong resolution-dependent decrease in the "sensitivity score" (the proportion of identified ARs that are correctly identified) as resolution increases, with over 25% of features being misclassified (relative to their training data set) as non-ARs at high resolution. Muszynski et al (2019) hypothesize that this is due to an interaction between the decrease in smoothness of the IWV field as resolution increases and the underlying topology-based method that they use to identify potential ARs.…”
Section: Spread Among Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Discussions following the 2 nd ARTMIP Workshop suggested that differences among AR tracking algorithms might reflect differences in expert opinion about what constitutes the boundary of ARs; resolving this question would require experts to hand-label ARs. Unrelated, but concurrent, advances in Computational Climate Science have demonstrated the utility of modern machine learning methods for tracking weather phenomena (Mudigonda et al 2017;Muszynski et al 2019;Kurth et al 2018). These developments also highlight the need for high-quality data to train machine learning methods: expert-labeled datasets.…”
mentioning
confidence: 99%